(untitled) (Global Journal of Science Frontier Research, 2018)
Corel Reef Ecosystems-The coral reef ecosystem is a collection of diverse species that interact with each other and with the physical environment. The latitudinal distribution of coral reef ecosystems in the oceans (geographical distribution) is determined by the seawater temperature, which influences the reproduction and growth of hermatypic coralsthe main component of the ecosystem. As so, coral reefs only occupy the tropical and subtropical zones. The vertical distribution (into depth) is limited by light. Sun light is the main energy source for this ecosystem, which is produced through photosynthesis of symbiotic microalgaezooxanthellae living in corals, macroalgae, seagrasses and phytoplankton.